FRI0351 DISTINCTION BETWEEN TELANGIECTASIA SECONDARY TO CONNECTIVE TISSUE DISEASE AND CUTANEOUS COLLAGENOUS VASCULOPATHY. (June 2019) - Walsh, Noreen; Moss, Phillip; Ly, Thaiyen; Pasternak, Sylvia; Green, Peter; Gallant, Chris; Lou Baxter, Mary; Kelly, Colleen; Burns, Ariel; Purdy, Kerri; Murphy, Elana; Hanly, John
Abstract : Background: Cutaneous collagenous vasculopathy (CCV), a recently described, rare, superficial dermal microangiopathy of unknown etiology, shares clinical and histopathological features in common with cutaneous lupus erythematosus and dermatomyositis. Fewer than 50 cases have been reported in the literature. Concurrence of CCV and connective tissue diseases (CTD) may present a diagnostic quandary. Objectives: To determine whether CCV cases at our center were associated with CTD and to identify distinguishing features between CCV and cutaneous manifestations of CTD. Methods: The laboratory information system at a single academic health care center (2000-2018) was searched to identify cases with a diagnosis of CCV. All pathological material and clinical charts were reviewed. The demographic, clinical and pathological data were documented. Results: We identified 6 cases of CCV (4 female, 2 male; median age 57 years). Clinically, a telangiectatic eruption was present in all patients, affecting the lower limbs and other sites (N= 5) and the abdomen and arms (N=1). All patients had been seen by a dermatologist and 3 by a rheumatologist. A concurrent CTD was present in 2 cases; Sjogrens syndrome (N=1) and undifferentiated connective tissue disease (N=1). In both, the clinical differential diagnosis included CCV and cutaneous involvement by the CTD. In all 6 cases, histopathological examination revealed a non-inflammatory vasculopathy, with PAS-positive, diastase resistant, hyaline thickening of ectatic superficial capillary walls, and loss of pericytes. These hallmarks of CCV excluded skin disease attributable to CTD in the two relevant cases. Conclusion: Concurrence of CCV and CTD, though uncommon, presents a diagnostic challenge. The clinical distribution of the CCV eruption, favouring the lower limbs, and its non-inflammatory character histopathologically distinguish it from cutaneous involvement by a CTD. Disclosure of Interests: Noreen Walsh: None declared, Phillip Moss: None declared, ThaiYen Ly: None declared, Sylvia Pasternak: None declared, Peter Green: None declared, Chris Gallant: None declared, Mary Lou Baxter: None declared, Colleen Kelly: None declared, Ariel Burns: None declared, Kerri Purdy: None declared, Elana Murphy: None declared, John Hanly Consultant for: Eli Lilly Canada.